Covalent polyester colouration by in situ chromophore creation. Issue 47 (11th May 2020) - Rowley, Jason V.; Exley, James; Yu, Huayang; Mircale, Gregory S.; Hayward, Adam S.; Thornton, Paul D.
Abstract : The covalent, in situ, colouration of a condensation polymer is disclosed as a template for simple and effective polyester colouration. Abstract : The permanent colouration of a polyester by straightforward azo coupling is disclosed. Uniquely, the chromophore is created only upon successful polymer modification with a non-coloured molecule ( in situ colouration), which confirms successful polymer adaptation and ensures that coloured waste is not produced. The method of colouration, which may feasibly be applied for the coloration of a wide-range of step-growth polyesters, yielded a polymer capable of preventing indigo deposition onto a range of fabrics, offering potential use within advanced detergent formulations.